Enhancing Data Security through Digital Image Steganography: An Implementation of the Two Least Significant Bits (2LSB) Method - Hakim, Fitro Nur; Sholikhan, Muhammad (International Journal of Graphic Design, 2024)
The rapid advancement of digital communication technologies has heightened the demand for robust data security methods, particularly for safeguarding sensitive information against cyber threats. Steganography, the art of concealing data within digital media, offers an effective means of securing communication by masking the very existence of hidden messages. This study evaluates the Two Least Significant Bits (2LSB) method as an enhancement to the conventional Least Significant Bit (LSB) technique, focusing on improving storage capacity and resistance to detection. The research employs a quantitative methodology, conducting experiments to analyze the impact of data embedding on image quality using metrics such as Mean Squared Error (MSE) and Peak Signal-to-Noise Ratio (PSNR). Data embedding was tested on images of varying sizes and resolutions, with results compared before and after embedding. The study also evaluates the system’s tolerance to compression and robustness against steganalysis attacks, such as histogram analysis and noise detection. The results demonstrate that the 2LSB method significantly enhances storage capacity while maintaining high image quality. For instance, PSNR values remained above 40 dB across all tested images, indicating minimal visual distortion. The method also showed resilience to lossless compression formats such as PNG, with minimal impact on data integrity. However, lossy compression formats like JPEG posed challenges in maintaining the embedded data. The MSE values before and after embedding were minor, ensuring that the hidden data remained undetectable under standard analysis. This research contributes to developing more efficient and secure steganography techniques, providing practical applications in protecting sensitive data during transmission. The findings underline the 2LSB method's potential as a viable solution for digital security, balancing enhanced storage capacity with robust resistance to detection. Future work should further explore integrating advanced encryption with 2LSB to strengthen data protection in diverse digital environments